Steroid synthesis and metabolism in the equine placenta during placentitis. Issue 3 (March 2020) - El-Sheikh Ali, H; Legacki, E L; Scoggin, K E; Loux, S C; Dini, P; Esteller-Vico, A; Conley, A J; Stanley, S D; Ball, B A
Abstract : Equine placentitis is associated with alterations in maternal peripheral steroid concentrations, which could negatively affect pregnancy outcome. This study aimed to elucidate the molecular mechanisms related to steroidogenesis and steroid-receptor signaling in the equine placenta during acute placentitis. Chorioallantois (CA) and endometrial (EN) samples were collected from mares with experimentally induced placentitis ( n = 4) and un-inoculated gestationally age-matched mares (control group; n = 4). The mRNA expression of genes coding for steroidogenic enzymes ( 3βHSD, CYP11A1, CYP17A1, CYP19A1, SRD5A1, and AKR1C23 ) was evaluated using qRT-PCR. The concentration of these enzyme-dependent steroids (P5, P4, 5αDHP, 3αDHP, 20αDHP, 3β-20αDHP, 17OH-P, DHEA, A4, and estrone) was assessed using liquid chromatography-tandem mass spectrometry in both maternal circulation and placental tissue. Both SRD5A1 and AKR1C23, which encode for the key progesterone metabolizing enzymes, were downregulated ( P < 0.05) in CA from the placentitis group compared to controls, and this downregulation was associated with a decline in tissue concentrations of 5αDHP ( P < 0.05), 3αDHP ( P < 0.05), and 3β-20αDHP ( P = 0.052). In the EN, AKR1C23 was also downregulated in the placentitis group compared to controls, and this downregulation was associated with a decline in EN concentrations of 3αDHP ( P < 0.01) and 20αDHP ( P < 0.05). Moreover, CA expression of CYP19A1 tended to be lower in the placentitis group, and this reduction was associated with lower ( P = 0.057) concentrations of estrone in CA. Moreover, ESR1 (steroid receptors) gene expression was downregulated ( P = 0.057) in CA from placentitis mares. In conclusion, acute equine placentitis is associated with a local withdrawal of progestins in the placenta and tended to be accompanied with estrogen withdrawals in CA.